Regression Analysis Of Jawarandu Goat Performance Given Corn Cob Silage Feed And Length Of Maintenance - Dias Harry Noviandy; Dede Kardaya; Dewi Wahyuni (Universitas Djuanda, 2025)
This research aims to determine the relationship model between the performance of jawarandu goats with the level of corn tebon silage feeding and the length of maintenance. The material used was 20 Jawarandu goats consisting of 4 treatments. The treatments given were field grass + corn tebon silage + concentrate with treatment levels P0 = 70% field grass 30% concentrate; P1 = 50% field grass, 20% corn tebon silage, 30% concentrate; P2 = 20% field grass, 50% corn tebon silage, 30% concentrate; P3 = 70% corn tebon silage, 30% concentrate. The results of this study were the average feed consumption of 684.15-908.94 g/head/day, average daily body weight gain of 68.00 g/day; 71.34 g/day; 77.02 g/day; 79.15 g/day, average feed conversion of 10.08 ± 2.16; 10.52 ± 2.38; 10.84 ± 1.78; and 10.61 ± 1.72, average feed cost per gain of Rp 20. 161.75 /kg; Rp 26,302.25/kg; Rp 27,105.74/kg; Rp 26,519.50/kg. After analyzing various regression models, the multiple linear regression model is a good model for research because the relationship between treatment and length of maintenance with feed consumption shows the coefficient of determination (R2) which is close to 1. The research concluded that the best treatment level in the study was the P3 treatment level in the 5th month with a daily body weight gain of 86.67 g/e/day with a feed conversion value of 9.53. The regression model that can be used for estimation of ration consumption from the treatment of corn tebon silage and length of maintenance is Y = 349.437 + 3.193X2 + 111.427X2, The value of the coefficient of determination (R2) which is close to 1 is on the feed consumption variable with a value of 0.982 or 98.2% which means that the closer to the number 1, the better the results